2013
DOI: 10.3109/07357907.2013.853075
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CAGene Mutations and Amplifications in Chinese Patients With Ovarian Clear Cell Carcinoma

Abstract: The role of genetic alterations in PIK3CA gene has not been fully explored in ovarian clear cell carcinoma (OCCC). The present study was undertaken to assess mutations and amplifications of exons 9 and 20 of PIK3CA in 51 Chinese OCCC patients. Activating missense mutations of PIK3CA were found in nine (17.6%) cases. One novel mutation T544P was identified in exon 9 which can increase AKT phosphorylation in cell culture. Amplifications of PIK3CA were observed in six cases (11.8%). PIK3CA mutations and amplifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The missense mutation does not change the protein activity, and we could speculate that E545A mutation in PIK3CA gene is not oncogenic in GCTB despite great evidences previously reported in other cancer models. Indeed, previous studies were pretending that E545A mutation is described as an oncogenic mutation in different types of cancer, such as breast and ovarian (Table 3) [73,74]. Furthermore, Gymnopoulos et al showed that mutations in PIK3CA, including E545A, gained function-induced oncogenic transformation (Table 3) (2007) [75].…”
Section: Discussionmentioning
confidence: 99%
“…The missense mutation does not change the protein activity, and we could speculate that E545A mutation in PIK3CA gene is not oncogenic in GCTB despite great evidences previously reported in other cancer models. Indeed, previous studies were pretending that E545A mutation is described as an oncogenic mutation in different types of cancer, such as breast and ovarian (Table 3) [73,74]. Furthermore, Gymnopoulos et al showed that mutations in PIK3CA, including E545A, gained function-induced oncogenic transformation (Table 3) (2007) [75].…”
Section: Discussionmentioning
confidence: 99%